The role of nationhood in citizenship education curricula: a comparison of Mexico and the Netherlands - van Lookeren Campagne, Kim (Trinity College (Dublin, Ireland). School of Education, 2022)
This paper aims to answer the research question: to what extent is nationhood an educational outcome in the prescribed national citizenship education curricula of secondary schools in Mexico and the Netherlands? This dissertation is a cross-national comparative discourse analysis of the citizenship education subjects ‘Civics and ethics formation’ (‘Formación Cívica y Ética’) and ‘Societal studies’ (Maatschappijleer). The framework is a critical approach to citizenship education that demonstrates that nationhood is an educational outcome of the curricula and identifies how both national and global citizenship play a role. The critical approach suggests that the aims of the national curricula are both to form norm-abiding national citizens and caring critical thinkers. Nationhood is connected to this aspect of socializing students into citizens. The Mexican curriculum demonstrates a more overt presence of nationhood through a discourse of “love for the nation”, while the Dutch curriculum has a more covert presence. The Dutch curriculum focuses on creating citizens of a “pluralistic” and “democratic” society, but this does appear to be another way of referring to the Netherlands. A brief comparison to the International Baccalaureate subject ‘Social and cultural anthropology’, which provides an example of a curriculum detached from nationhood, reveals that aims of citizenship education may also be reached without the emphasis on nationhood. These aims include shaping individuals who care for and participate in their social and natural environment, locally and globally.
Keywords: Critical Perspectives on Education; Education